(3JMdjd hJUeje GdfXes - (3GdUjQaj(B, (3eMeOs ((3GdGScfOQjI(B;(3GdbGgQI(B,(3eDSSI WjHIs (3eDSSI MhQS GdOhdjIs, 2005)
(3fXe GdeYdheGJ GdeMShHI, JMdjd fXe GdeYdheGJ, JUeje fXGe GdeYdheGJ JWHjb hGNJHGQ fXGe GdeYdheGJ(B.s
Keywords: (3JMdjd GdfXes; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s